Railway integration into Prague public transportation - Králík, Jiří (2012)
The purpose of this thesis is charting and analyzing railway services integrated to Prague's public transportation system. Its current integration and effiency will be evaluated based on a study of professional literature and after that, changes and optimizations will be proposed in order to increase the transportation quality. "I'm looking towards inspiration from foreign train lines as well as with opinions of travelers and commuters.